Efektifitas Olahraga Aerob Intensitas Berat Dalam Meningkatkan Kadar High Density Lipoprotein (HDL) Plasma - Aldila Akhadiyati Narwienda; . Kiyatno; Sinu Andhi Yusuf (Nexus Biomedika, 2013)
Background: The value of regular aerobic exercise in increasing HDL level of plasma has accepted widespread acceptance. In contrast, the only few studies have examined the effect of HDL-C level to exercise training. The objective of this study was to determine the most effective intensity of the aerobic exercise in increasing HDL plasma level. Method: This was an experimental laboratory study with randomized pre-test and post-test control group design. This study was conducted from April to June 2012 at Laboratory of Physiology FK UNS. Forty subjects were divided into four groups based on purposive sampling method. There were control group, mild-intensity group, moderate-intensity group and high-intensity group. The HDL level tests were taken before and after eight weeks of intervention. The results then were analyzed with one-way ANOVA test. Results: Based on one-way ANOVA test, there was significant difference among groups in the study (p = 0.002). Based on multiple comparison analyzes, (1) there was no significant difference between the raise of HDL plasma level in control group and mild-intensity group (p = 0.749), (2) there was significant difference between the raise of HDL plasma level in control group and moderate-intensity group (p = 0.044), and (3) there was significant difference between the raise of HDL plasma level in control group and high-intensity group (p = 0.002). Conclusions: High-intensity aerobic exercise was the most effective in increasing the HDL plasma level. Keywords: HDL, aerobic exercise, intensity